Peningkatan Keterampilan Membaca Pemahaman Menggunakan Metode PQ4R Siswa Kelas VB SD Negeri 1 Gemawang - Ratih Trias Finiza; Shanta Rezkita; Haning Susilo Wardani (Jurnal Ilmiah Profesi Guru (JIPG), 2021)
Reading comprehension skills are very important for students. Based on the results of observations and interviews, it shows that students find it difficult to understand a reading. The purpose of this study was to test the improvement of reading comprehension skills using the PQ4R method in class VB students at SD Negeri 1 Gemawang. This type of research is Classroom Action Research (CAR) which consists of two cycles. This increase can be seen from the average value of understanding in the first cycle of 64.8 in the good category and increased in the second cycle to 74.03 in the good category. The above results are reinforced by the results of observations of student learning activities. The average percentage value in the first cycle was 65.76% in the good category and increased in the second cycle to 72.49% in the good category. The results of the analysis concluded that the use of the PQ4R method could improve the reading comprehension skills of VB students at SD Negeri 1 Gemawang. Based on these results, the use of the PQ4R method can be used for further research with the hope that it can function as a problem solving in learning in elementary schools. Keywords: PQ4R method; Reading comprehension; Indonesian